Biochemical characterization of solid state fermented maize cob (Zea mays) using Rhizopus oligosporusand its application in poultry feed production - Amaka Ndego; Theresa Ezedom; Egoamaka Egbune; Nyerhovwo Tonukari (International Journal of Recycling of Organic Waste in Agriculture)
Purpose This study aimed to evaluate the biochemical characterization of solid state fermented maize (Zea mays) cob and its use in poultry feed production.Method Solid state fermentation was carried out at room temperature for 72 hours using Rhizopus oligosporus inoculum with a well prepared phosphate buffer (50 mM , pH 6).Results Results showed a significant (p< 0.05) increase in glucose and decrease in sugars and soluble proteins concentration in the R. oligosporus fermented maize cob. At 10% inoculum, the highest concentrations of glucose, reduced sugars and soluble proteins were 1.15±0.21, 45.7±0.6 and 12.9±0.3 mg g-1, respectively. Similarly, the total phenol, flavonoid content and antioxidant activity of 2,2-diphenyl-1-picrylhydrazyl (DPPH) and amylase activity of maize cob increased significantly (p < 0.05) with fermentation. Broiler chickens fed with fermented maize cob of 10% inoculum had the same weight gain as the control (1.4±0.1kg). Fermentation did not induce a significant difference (p<0.05) in the activities of serum aspartate aminotransferase (AST), alanine aminotransferase (ALT) and alkaline phosphatase (ALP).Conclusion The observed increase in proteins and sugars in the fermented products suggests their suitability as excellent components for animal feed production. Thus, the livestock feed formulation industries might benefit from the usage of fermented maize cob as a raw material in animal feeds as well as a protein fortifier.